Mendiskusikan Konstruksi Kritik Tafsir; Sejarah, Bentuk, Landasan Hukum, Prinsip dan Parameternya - Muhammad Ulinnuha (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2024)
This paper attempts to address the discourse of interpretive criticism; starting from the definition, history, legal basis to the principles and parameters of criticism. To get a clear description, a historical approach with descriptive-philosophical methods is used. This study comes to the conclusion that critique of interpretation is scientific and systematic steps to carry out analysis, and evaluation of the interpretation of the Qur'an. Normatively, the legal basis of interpretation criticism can be traced in the Qur'an, the Sunnah of the Prophet, the opinion of friends and scientific principles. As for the principles and parameters of interpretive criticism that need to be guided by being fair and proportionate, being moderate, knowing aspects of qaṭ'īyāt, not violating ijma' (consensus), paying attention to customary norms (al-'urf), paying attention to context (siyāq), consider the benefits, dan use logic (manṭiq).